Anti-leaders(hip) in Social Movement Organizations: The case of autonomous grassroots groups. (November 2014) - Sutherland, Neil; Land, Christopher; Böhm, Steffen
Through the Arab Spring and the Occupy movement, the idea of horizontal, leaderless organization has come to the attention of the mass media. In this article we explore radical, participative-democratic alternatives to leadership through an empirical study of four Social Movement Organizations (SMOs). Whilst there has been some writing on leadership within SMOs, it has mirrored the 'mainstream' assumption that leadership is the product of individual leaders possessing certain traits, styles and/or behaviours. In contrast, critical leadership studies (CLS) recognize that leadership is a relational, socially constructed phenomenon rather than the result of a stable set of leadership attributes that inhere in 'the leaders'. We utilize this framing to analyse how leadership is understood and performed in anarchist SMOs by examining how actors manage meaning and define reality without compromising the ideological commitments of their organizations. Furthermore, we also pay attention to the organizational practices and processes developed to: (a) prohibit individuals from permanently assuming a leadership role; (b) distribute leadership skills and roles; and (c) encourage other actors to participate and take-up these roles in the future. We conclude by suggesting that just because an organization is leaderless, it does not necessarily mean that it is also leadershipless.